2012
DOI: 10.1155/2012/359869
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesviridae Methods of Natural Killer Cell Evasion

Abstract: Human herpesviruses cause diseases of considerable morbidity and mortality, ranging from encephalitis to hematologic malignancies. As evidence emerges about the role of innate immunity and natural killer (NK) cells in the control of herpesvirus infection, evidence of viral methods of innate immune evasion grows as well. These methods include interference with the ligands on infected cell surfaces that bind NK cell activating or inhibitory receptors. This paper summarizes the most extensively studied NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 131 publications
0
12
0
Order By: Relevance
“…In the case of KSHV, K5 selectively removes HLA-A and HLA-B allotypes, while K3 targets HLA-A, HLA-B, HLA-C, and HLA-E (22). In addition, the removal of ligands for activating receptors on NK cells is a common way for viruses to prevent NK cell activation (65), and KSHV encodes several factors, including K5, that reduce the surface expression of such receptors (9,10,33). The distinct timing and substrate specificities of K3 and K5 suggest that allotype-specific downregulation of MHC class I molecules occurs during the immediate early stage of lytic replication, while indiscriminant and extensive reduction of surface MHC class I molecules is confined to later stages.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of KSHV, K5 selectively removes HLA-A and HLA-B allotypes, while K3 targets HLA-A, HLA-B, HLA-C, and HLA-E (22). In addition, the removal of ligands for activating receptors on NK cells is a common way for viruses to prevent NK cell activation (65), and KSHV encodes several factors, including K5, that reduce the surface expression of such receptors (9,10,33). The distinct timing and substrate specificities of K3 and K5 suggest that allotype-specific downregulation of MHC class I molecules occurs during the immediate early stage of lytic replication, while indiscriminant and extensive reduction of surface MHC class I molecules is confined to later stages.…”
Section: Discussionmentioning
confidence: 99%
“…This co-existence led to the development of opposite mechanisms in which the NK cells try to kill the infected cells and the viruses on the other hand try to escape such killing [32]. Famous among these viruses are viruses of the Herpesviride that had developed numerous immune evasion mechanisms such as the use of viral miRNAs in order to escape NK cell attack [23], [24], [33]. Hence, we were quite surprised to observe that no changes were detected in the expression of the NK ligands tested, after transduction with 21 miRNAs of HSV-2 and that increased NK cell killing was observed following HSV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Differences from healthy controls (HC) have, however, been suggested by some studies of the immune system. Several groups have described a decrease in cytotoxic activity of natural killer (NK) and T cells, predominantly by the reduction of granzyme or perforin levels , similar to which is also associated commonly with herpes virus infections . In contrast, Curriu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Differences from healthy controls (HC) have, however, been suggested by some studies of the immune system. Several groups have described a decrease in cytotoxic activity V C 2016 British Society for Immunology, Clinical and Experimental Immunology, 184: 237-247 of natural killer (NK) and T cells, predominantly by the reduction of granzyme or perforin levels [10][11][12][13], similar to which is also associated commonly with herpes virus infections [14]. In contrast, Curriu et al found an increase of NKp46 (natural cytotoxicity on NK cells) and CD69 (activation marker) expression on NK cells [15].…”
Section: Introductionmentioning
confidence: 99%